(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article deals with key prospects and challenges in compiling and reporting on sustainable development, describing trends in its distribution. The author summarizes the key benefits of reporting on sustainable development on stakeholders levels – corporate, regional andmacro level. A challenges in reporting on sustainable development in the context of the general problems of presentation, quality assurance and verification of such reportsare discussed.Particular attention is paid to the sharing of sustainability reporting among the world’s leading companies, despite the fact that an integrated format for its provision was still on little demand. The main focus in sustainability reporting considered by authoris the standardization of approaches to its compilation, provision, confirmation by independent third parties and interpretation.